Changes in the immune response against SARS-CoV-2 in individuals with severe COVID-19 treated with high dose of vitamin D - Torres, Montserrat; Casado, Guiomar; Vigon, Lorena; Rodríguez-Mora, Sara; Mateos, Elena; Ramos-Martín, Fernando; López Wplf, Daniel; Sanz-Moreno, José; Ryan-Murua, Pablo; Taboada-Martínez, María Luisa; López-Huertas, María Rosa; Cervero, Miguel; et al. (Elsevier, 2022)
Main cause of severe illness and death in COVID-19 patients appears to be an excessive but ineffectual inflammatory immune response that may cause severe acute respiratory distress syndrome (ARDS). Vitamin D may favour an anti-inflammatory environment and improve cytotoxic response against some infectious diseases. A multicenter, single-blind, prospective, randomized clinical trial was approved in patients with COVID-19 pneumonia and levels of 25-hydroxyvitamin D (25(OH)D) of 14.8 ng/ml (SD: 6.18) to test antiviral efficacy, tolerance and safety of 10,000 IU/day of cholecalciferol (vitamin D3) for 14 days, in comparison with 2000 IU/ day. After supplementation, mean serum 25(OH)D levels increased to 19 ng/ml on average in 2000 IU/day versus 29 ng/ml in 10,000 IU/day group (p < 0.0001). Although levels of inflammatory cytokines were not modified by treatment with 10,000 IU/day, there was an increase of anti-inflammatory cytokine IL-10 and higher levels of CD4+ T cells, with predominance of T central memory subpopulation. Cytotoxic response against pseudotyped SARS-CoV-2 infected cells was increased more than 4-fold in patients who received 10,000 IU/day. Moreover, levels of IFN¿ were significantly higher in this group. Beneficial effect of supplementation with 10,000 IU/day was also observed in participants who developed ARDS and stayed at the hospital for 8.0 days, whereas those who received 2000 IU/day stayed for 29.2 days (p = 0.0381). Administration of high doses of vitamin D3 as adjuvant of the standard care treatment during hospitalization for COVID-19 may improve the inflammatory environment and cytotoxic response against pseudotyped SARS-CoV-2 infected cells, shortening the hospital stay and, possibly, improving the prognosis.